Blastic Plasmacytoid Dendritic Cell Neoplasm Mimicking Erythema Nodosum: A Case Report - Marino Hirata; Nozomu Yoshino; Maya Takazawa; Hisashi Oshiro; Shinichi Kako; Hitoshi Sugawara (Annals of Internal Medicine: Clinical Cases)
Blastic plasmacytoid dendritic cell neoplasm (BPDCN), previously known as blastic natural killer cell lymphoma, is a rare, difficult-to-diagnose, and aggressive hematologic malignancy. Skin lesions are the initial presentation of BPDCN in 64% to 77% of cases, characterized by brown to purple nodular or bruised macular lesions in solitary or multiple locations. Here, we report the case of a 57-year-old man who initially presented with refractory erythema nodosum symptoms, including fever, arthritis, and painful erythema, and was finally diagnosed with BPDCN after a second skin biopsy. This case illustrates that skin lesions caused by BPDCN mimic ordinary erythema nodosum.